2024
DOI: 10.1002/idm2.12141
|View full text |Cite
|
Sign up to set email alerts
|

Single‐atom materials: The application in energy conversion

Chenxi Zhu,
Jiarui Yang,
Jiangwei Zhang
et al.

Abstract: Single‐atom materials (SAMs) have become one of the most important power sources to push the field of energy conversion forward. Among the main types of energy, including thermal energy, electrical energy, solar energy, and biomass energy, SAMs have realized ultra‐high efficiency and show an appealing future in practical application. More than high activity, the uniform active sites also provide a convincible model for chemists to design and comprehend the mechanism behind the phenomenon. Therefore, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…The N 1s XPS spectrum of FePc@TiO 2 reveals the coexistence of four types of N species: graphitic N (401.8 eV), pyrrolic N (399.9 eV), Fe–N (399.3 eV), and pyridinic N (398.1 eV) (Figure S6a). The Ti 2p XPS spectrum of FePc@TiO 2 (Figure S8b) shows characteristic Ti 2p 3/2 and Ti 2p 1/2 peaks at 458.7 and 464.2 eV, respectively, which are indicative of the Ti 4+ oxidation state. Compared with the peaks of pristine TiO 2 , these peaks exhibit positive shifts of 0.30 and 0.32 eV, respectively, which may be attributed to lattice distortions, corresponding to the symmetry disruption as evidenced by XANES.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N 1s XPS spectrum of FePc@TiO 2 reveals the coexistence of four types of N species: graphitic N (401.8 eV), pyrrolic N (399.9 eV), Fe–N (399.3 eV), and pyridinic N (398.1 eV) (Figure S6a). The Ti 2p XPS spectrum of FePc@TiO 2 (Figure S8b) shows characteristic Ti 2p 3/2 and Ti 2p 1/2 peaks at 458.7 and 464.2 eV, respectively, which are indicative of the Ti 4+ oxidation state. Compared with the peaks of pristine TiO 2 , these peaks exhibit positive shifts of 0.30 and 0.32 eV, respectively, which may be attributed to lattice distortions, corresponding to the symmetry disruption as evidenced by XANES.…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery by Jasinski in 1964 that transition metal phthalocyanine (MPc) compounds can catalyze the ORR, transition metal–nitrogen–carbon (TM–N–C) catalytic materials have been extensively reported and are considered one of the most promising nonplatinum catalysts currently under development. In recent decades, the activity of TM–N–C catalysts has greatly improved from intrinsic activity to the density of active sites, and is currently in a bottleneck stage. Recent research has shown that the catalytic efficiency of TM–N–C catalysts is intricately linked to the spin state of transition metals, a relationship particularly pronounced in 3d transition metals, as evidenced by empirical research. However, due to the amorphous nature of M–N–C, it is impossible to form a neatly arranged magnetic domain structure, usually exhibiting paramagnetism (PM), which does not optimally fit 3 O 2 absorption. Therefore, designing the spin configuration of M–N–C to achieve a ferromagnetic exchange interaction has become an effective method to break through the current bottleneck and is also a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CSA-NCs have not only found applications in electrocatalysis but also shown potential in catalyzing crucial processes in energy-storage systems like ultracapacitors, lithium-ion batteries, and sodium−sulfur energy devices. 31 Over the span of a mere decade, we have witnessed a remarkable surge of interest and advancement in CSA-NCs for electrochemical energy applications. Simultaneously, a number of previously published reviews on this subject have concentrated on aspects such as the reaction pathways of EORR, ENRR and ECO 2 RR, 32−35 the engineering of singleatom material synthesis, 36,37 and the exploration of metalbased electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The impressive progress in CSA-NCs has positioned them as promising candidates to outpace conventional metal nanoparticle materials for renewable energy applications. Moreover, CSA-NCs have not only found applications in electrocatalysis but also shown potential in catalyzing crucial processes in energy-storage systems like ultracapacitors, lithium-ion batteries, and sodium–sulfur energy devices …”
Section: Introductionmentioning
confidence: 99%
“…A strategy involving reactor cascades, encompassing two separate systems corresponding to sequential CO 2 -to-CO and CO-to-C 2+ steps, has been implemented. , Despite its potential to boost selectivity for carbon-intensive products, reactor cascade systems encounter challenges related to operability, stability, high cost, and energy consumption. An alternative approach, tandem catalysis, couples independent single-atom sites for CO generation with Cu sites for subsequent deep reduction reactions, which effectively decouples multiple steps and increases the accessible CO concentration around Cu surfaces. , Notably, Ni single-atom (Ni-SA) catalysts have been shown to achieve efficient CO 2 RR performance with over 90% selectivity for CO production. Furthermore, the spatial arrangement of these two sites can greatly affect the local CO concentration and the utilization efficiency of CO intermediates. , However, previous tandem strategies usually adopt the coplanar design, which encounters challenges associated with slow mass transfer and short residence time of CO, ultimately reducing the CO coverage on the Cu surface. Therefore, optimizing the spatial distribution of the different catalytic sites along the direction of the gas channel is critical to effectively overcome mass transport of CO and increase local CO enrichment.…”
Section: Introductionmentioning
confidence: 99%